دور التخطيط الإستراتيجي على أداء المنظمات الحكومية الإقتصادية في أبوظبي من خلال الإستدامة وريادة المنظمات كمتغير الوسيط - ماجد راشد محمد المنصوري
This study aims to identify the role of strategic planning in the performance of government economic organizations in Abu Dhabi, as well as the mediating role of sustainability and leadership in organizations in Abu Dhabi. Clear goal setting and strategic planning are characterized by critical roles for general managers that are closely linked to measuring and improving organizational performance. where the descriptive analytical method was relied upon, and the quantitative method was also used. The study population consisted of employees in the Department of Economic Development in Abu Dhabi, in the United Arab Emirates, who numbered 84,282 employees, and a stratified random sample of 307 individuals was taken, which included departments of all kinds (top management, middle management, and lower management). A total of 308 questionnaires were distributed to the respondents; 279 questionnaires were received, and the 12 outliers were completed. The data was also analyzed using SPSS software, as well as Smart PLS. The study produced a set of results, the most important of which is the existence of a statistically significant relationship between strategic planning and sustainability and that strategic planning has a statistically significant impact on sustainability in the Department of Economic Development in Abu Dhabi. It was also found that an increase in strategic planning leads to an increase in entrepreneurship, and that an increase in strategic planning has a positive impact on performance. The increase in strategic planning is also driving an increase in sustainability at the Abu Dhabi Department of Economic Development. The study recommended a set of recommendations, the most important of which are: the need to pay special attention to strategic planning because it has an impact on the sustainability of organizations and the prosperity of their performance; the need to develop plans and strategies that contribute to the development of working departments; and the need to have effective training programs that contribute to creating complete knowledge among employees.